HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN PERILAKU SELF DIAGNOSIS KESEHATAN REPRODUKSI BERBASIS ARTIFICIAL INTELLEGENCE (AI) PADA GENERASI Z - Fitri Kurnia Rahim; Icca Stella Amalia; Bunga Farida; Lidiyah Lidiyah; Nadila Salsabila (Yayasan Haiah Nusratul Islam, Indonesia, 2026)
Background: Artificial Intelligence (AI) has increasingly been used by adolescents as a source of health information, including for reproductive health self-diagnosis. Although AI offers rapid and accessible information, its use without adequate health literacy may lead to misinterpretation, anxiety, and inappropriate health decisions. Therefore, it is essential to examine the relationship between adolescents’ knowledge and attitudes and their self-diagnosis behavior using AI. Method: This study employed a quantitative approach with a cross-sectional design. A total of 81 tenth-grade students at SMAN 9 Kota Cirebon were selected using cluster sampling. Data were collected through a structured questionnaire measuring knowledge, attitudes, and AI-based self-diagnosis behavior. Data analysis included univariate and bivariate analysis using the Chi-Square test with a significance level of 0.05. Results: Most respondents had used AI as a health information source (96.3%). The majority demonstrated a moderate level of knowledge (81.5%), positive attitudes toward AI use (98.8%), and moderate self-diagnosis behavior (53.1%). Statistical analysis revealed a significant association between knowledge and AI-based self-diagnosis behavior (p = 0.000), while attitudes showed no significant association (p = 0.639). Conclusion: Knowledge significantly influences adolescents’ self-diagnosis behavior using AI, whereas attitudes do not show a significant relationship. Strengthening health and digital literacy is crucial to ensure that AI use supports, rather than replaces, professional medical consultation.